2021
DOI: 10.1063/5.0035568
|View full text |Cite
|
Sign up to set email alerts
|

A supersonic laser ablation beam source with narrow velocity spreads

Abstract: A supersonic beam source for SrF and BaF molecules is constructed by combining the expansion of carrier gas (a mixture of 2% SF6 and 98% argon) from an Even–Lavie valve with laser ablation of a barium/strontium metal target at a repetition rate of 10 Hz. Molecular beams with a narrow translational velocity spread are produced at relative values of Δv/v = 0.053(11) and 0.054(9) for SrF and BaF, respectively. The relative velocity spread of the beams produced in our source is lower in comparison with the results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 48 publications
2
25
0
Order By: Relevance
“…This regime arises as the ratio of the rotational constant to the natural linewidth decreases due to increasing molecular mass and size. Additionally, since photon spin molasses is not efficient for cooling molecules with rotational quanta above the capture range J c , it is likely that pre-cooling with another method such as supersonic expansion [33][34][35], buffer gas cooling [36][37][38][39][40], or sympathetic collisional cooling by laser-cooled atoms [41] would be advantageous and could extend the reach of these techniques to the sub-mK regime.…”
Section: Discussionmentioning
confidence: 99%
“…This regime arises as the ratio of the rotational constant to the natural linewidth decreases due to increasing molecular mass and size. Additionally, since photon spin molasses is not efficient for cooling molecules with rotational quanta above the capture range J c , it is likely that pre-cooling with another method such as supersonic expansion [33][34][35], buffer gas cooling [36][37][38][39][40], or sympathetic collisional cooling by laser-cooled atoms [41] would be advantageous and could extend the reach of these techniques to the sub-mK regime.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has shown that using a gas source for the halide, for example SF 6 , can successfully generate metal halides like AlF. 91 To produce a source of Cl atoms, Cl 2 , HCl or possibly methanochlorides like CCl 4 , CHCl 3 and CH 2 Cl 2 would be reasonable candidates. There is a previous report of AlCl being produced by ablation of an Al rod exposed to Cl 2 gas, 92 but its characteristics were not described in detail.…”
Section: Discussionmentioning
confidence: 99%
“…III A 1). Traditional molecular beam experiments typically employ supersonic beam expansion to obtain a source of translationally cold molecules with a narrow velocity spread [61,62]. This is a straightforward, easily generalizable technique since adiabatic cooling due to the sudden expansion of a gas rests on thermodynamic principles and is therefore agnostic to the finer details of the molecular species.…”
Section: Direct Laser Coolingmentioning
confidence: 99%